2005
DOI: 10.1093/nar/gki226
|View full text |Cite
|
Sign up to set email alerts
|

Licensing for DNA replication requires a strict sequential assembly of Cdc6 and Cdt1 onto chromatin in Xenopus egg extracts

Abstract: Replication origins are licensed for a single initiation event by the loading of Mcm2-7 proteins during late mitosis and G1. Sequential associations of origin recognition complex, Cdc6 and Mcm2-7 are essential for completion of the licensing. Although Cdt1 also binds to the chromatin when the licensing reaction takes place, whether the binding is a requirement for Cdt1 to function is unclear. To analyze the relevance of the chromatin association of Cdt1, we carried out chromatin transfer experiments using eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 47 publications
1
45
0
1
Order By: Relevance
“…This idea is in agreement with Palacios DeBeer et al (2003), who demonstrate that origin and HM silencer ACS differ in their affinity for the ORC and that this difference reflects the preferential function of the corresponding ACS in silencing or origin firing. We propose that an additional functional dissimilarity of these two types of ACS is their dependence on the cdc6-1 allele (Figure 3) (Weinreich et al 2001;Tsuyama et al 2005). It is possible that the surrounding sequence of core X-and Y9-elements influences the ACS silencing specificity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This idea is in agreement with Palacios DeBeer et al (2003), who demonstrate that origin and HM silencer ACS differ in their affinity for the ORC and that this difference reflects the preferential function of the corresponding ACS in silencing or origin firing. We propose that an additional functional dissimilarity of these two types of ACS is their dependence on the cdc6-1 allele (Figure 3) (Weinreich et al 2001;Tsuyama et al 2005). It is possible that the surrounding sequence of core X-and Y9-elements influences the ACS silencing specificity.…”
Section: Discussionmentioning
confidence: 94%
“…Cdc6p is essential for the loading of the MCM complex on ORC-bound ACS at origins of replication (Blow and Dutta 2005). The cdc6-1 allele impairs DNA replication (Weinreich et al 2001;Tsuyama et al 2005). However, it selectively caused derepression only in the ACS-less GF2 and GF3 constructs, while having negligible effects on the ACS-containing constructs ( Figure 3G).…”
Section: Discussionmentioning
confidence: 99%
“…To address GST-Cdt1-induced loading of replication-related proteins onto overreplicating chromatin, sperm nuclei (22,000 nuclei) were incubated with egg extracts (18 l) for 90 min, the reaction mixture was supplemented with GST-Cdt1, caffeine, and/or Gem79-130, and the reaction volume was adjusted to 22 l. The samples were further incubated for 30 or 90 min. The resulting chromatin fractions were isolated and immunoblotted as described previously (Tsuyama et al, 2005).To examine the phosphorylation of Chk1 by immunoblotting, nuclei in egg extracts were isolated as described previously (Kumagai et al, 1998), with a slight modification. After a 90-min incubation of Xenopus egg extracts with sperm nuclei (34,000 nuclei in 29 l), the reaction mixture was further incubated for 90 min with 5 l of buffer or GST-Cdt1 in the presence or absence of caffeine or Gem79-130.…”
mentioning
confidence: 99%
“…In contrast, elimination of Cdc6 interferes with Cdt1 origin binding in vitro (Randell et al 2006;). Studies in Xenopus extracts have shown that Cdt1 associates with chromatin in the absence of Cdc6 (Gillespie et al 2001;Tsuyama et al 2005); however, only Cdt1 associated in the presence of Cdc6 is able to contribute to Mcm2 -7 loading (Tsuyama et al 2005). Consistent with a robust interaction between Cdc6 and ORC, a complex between the proteins has been structurally characterized (Speck et al 2005;Sun et al 2012) and origin-bound ORC stimulates Cdc6 ATP hydrolysis (Randell et al 2006).…”
Section: Origin Recognitionmentioning
confidence: 98%
“…Biochemical studies support a model in which ORC first interacts with Cdc6 and this complex then recruits Cdt1 and Mcm2 -7. Loss of Cdt1 does not prevent Cdc6 chromatin association in vivo or origin recruitment in vitro (Maiorano et al 2000;Nishitani et al 2000;Tsuyama et al 2005;Randell et al 2006;). In contrast, elimination of Cdc6 interferes with Cdt1 origin binding in vitro (Randell et al 2006;).…”
Section: Origin Recognitionmentioning
confidence: 99%